2014
DOI: 10.1016/j.ijdevneu.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of EEG frequency maturation and power changes in children on the Russian North

Abstract: The aim of the study was to reveal longitudinal changes in electroencephalogram spectral power and frequency (percentage frequency composition of EEG and alpha peak frequency) patterns in normal children from northern Russia. Fifteen children (9 girls and 6 boys) participated in the study. The resting state (eyes closed) EEGs were recorded yearly (2005-2013) from age 8 to age 16-17 for each child. EEG frequency patterns were estimated as the percentages of waves with a 1 Hz step revealed by measuring the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
(75 reference statements)
2
15
0
Order By: Relevance
“…Studies have shown that from early childhood to late adolescence [healthy human subjects (2.4–19.4 years)], the location of maximal SWS activity during sleep shifts from posterior to anterior regions as the brain matures [ 17 , 48 ]. Our automated algorithm identified occipital predominance of SWS in qEEG of RTT and control females below 10 yrs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that from early childhood to late adolescence [healthy human subjects (2.4–19.4 years)], the location of maximal SWS activity during sleep shifts from posterior to anterior regions as the brain matures [ 17 , 48 ]. Our automated algorithm identified occipital predominance of SWS in qEEG of RTT and control females below 10 yrs.…”
Section: Discussionmentioning
confidence: 99%
“…All these factors can have an impact on the separation of theta and alpha bands (Klimesch, 1999 ; Garn et al, 2012 ; Grandy et al, 2013a ; Bazanova and Vernon, 2014 ). Research shows that alpha power is lower in early childhood and in the elderly than in adulthood (Chiang et al, 2011 ; Cottone et al, 2013 ; Grandy et al, 2013b ; Ponomareva et al, 2013 ; Soroko et al, 2014 ; Vysata et al, 2014 ; Miskovic et al, 2015 ; Zappasodi et al, 2015 ), and that alpha peak frequency is higher in females than in males in posterior parts of the brain (Langrova et al, 2012 ; Garces et al, 2013 ). Moreover, alpha power decreases and theta power increases during the transition from wakefulness to sleep (Klimesch, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of averaged non-artifact epochs for the power spectra analysis were balanced within the subjects and were set to 45. The estimations of the absolute power of the EEG were calculated and averaged in the following frequency bands: delta (1.5-4 Hz), theta (4-7.5 Hz), alpha1 (7.5-9.5 Hz), alpha2 (9.5-12.5 Hz), beta1 (12.5-18 Hz) and beta2 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Estimation arrays were averaged for each subject in each year and were subjected to standardization by means of transformations, Y = log X for power [27], for further statistical analysis.…”
Section: The Procedure Eeg Data Acquisition and Analysismentioning
confidence: 99%
“…Since the spectral power of EEG rhythms is influenced not only by the index of these rhythms, but also by the amplitude-consideration of the frequency structure and spectral power of EEG gives a broader perspective to the estimation of the neurophysiological mechanisms of cognitive activities and individual differences. For the frequency structure evaluation, the interval durations were measured between the points crossing the zero (isoline) using a curve by means of S.S. Bekshaev's (IEPhB RAS) program [20,28]. The interval durations (ms) between points on the isoline intersections were transformed into frequencies (Hz) and evaluated across all analyzed EEG intervals (no less than 3 min).…”
Section: The Procedure Eeg Data Acquisition and Analysismentioning
confidence: 99%
See 1 more Smart Citation